Molecular relaxation processes in calf-thymus DNA, in the presence of Mn2+ and Na+ ions: A Raman spectroscopic study. Issue 5 (2008) - Muntean Muntean, Cristina M. Cristina M.; Bratu Bratu, Ioan Ioan
Abstract : In this paper the Raman total half bandwidths of calf-thymus DNA vibrations have been measured as a function of Mn 2+ ion concentration (0–600 mM), in the presence of two concentrations of Na + cations, respectively. The dependencies of the half bandwidths and of the global relaxation times on DNA molecular subgroup structure, on Mn 2+ and Na + ions concentrations, respectively, are reported. It is shown that changes in the (sub)picosecond dynamics of molecular subgroups in calf-thymus DNA can be monitored with Raman spectroscopy. In this study the Raman band parameters for the vibrations at 729 cm -1 (dA), 787 cm -1 (dC), 1094 cm -1 (PO2 - ), 1376 cm -1 (dA, dG, dT, dC), 1489 cm -1 (dG, dA) and 1578 cm -1 (dG, dA) of calf thymus DNA are presented. The full-widths at half-height (FWHH) of the bands in calf-thymus DNA are typically in the wavenumber range from 9 to 33.5 cm -1 . It can be observed that the molecular relaxation processes studied in this work, have a global relaxation time smaller than 1.179 ps and larger than 0.317 ps. Mn 2+ -induced DNA structural changes result for the vibrations at 729 cm -1 and 787 cm -1 in smaller global relaxation times, and larger half bandwidths, respectively, as compared to the starting value of 0 mM Mn 2+ . The vibrational energy transfer processes of these two subgroups (dA, dC), respectively, are slower in the case of DNA samples at 10 mM NaCl, as compared to the corresponding DNA samples at 150 mM NaCl. However, the behaviour of the global relaxation times characteristic to the bands at 729 and 787 cm -1 is similar with respect to manganese(II) ions concentration, in the case of the two values of Na + ions content, respectively. On the contrary, the molecular dynamics is slower for the base vibrations at 1376, 1489 and 1578 cm -1, in the case of DNA samples at 150 mM NaCl, as compared to the corresponding samples at lower Na + concentration, in almost all Mn 2+ ions concentration range. The molecular relaxation processes in these three cases, respectively, are quite different for the corresponding samples with different Na + ions content, upon increasing divalent manganese ions concentration. The molecular dynamics characterizing the band near 1094 cm -1 of the DNA backbone PO2 - symmetric stretching vibration is faster upon increasing the Mn 2+ ions concentration between 0–600 mM and seems not to be influenced by the Na + ions content, specific to our experimental conditions.